Core-hole effects on energy-loss near-edge structure - Duscher, G.; Buczko, R.; Pennycook, S.J.; Pantelides, S.T. (Ultramicroscopy, 2001)
We present first-principles electron energy-loss near-edge structure calculations that incorporate electron–hole interactions and are in excellent agreement with experimental data obtained with X-ray absorption spectroscopy (XAS) and electron energy-loss spectroscopy (EELS). The superior energy resolution in XAS spectra and the new calculations make a compelling case that core-hole effects dominate core-excitation edges of the materials investigated: Si, SiO 2, MgO, and SiC. These materials differ widely in the dielectric constant leading to the conclusion that core–hole effects dominate all core-electron excitation spectra in semiconductors and insulators. The implications of the importance of core-holes for simulations of core-electron excitation spectra at interfaces will be discussed.